KETERKAITAN KEAMANAN PANGAN DAN WORLD TRADE ORGANIZATION DALAM ASPEK KULTURAL, ILMU PENGETAHUAN DAN TEKNOLOGI - Sylvia Laksmi Sardy (Badan Standardisasi Nasional, 2005)
Recently, international trade regime has rejected cultural perceptions of what is safe to eat, overturning millennial of tradition. In WTO Agreement on Sanitary and Phytosanitary Measures (SPS), science has been used as the arbiter in resolving disputes related to food safety. However, the SPS Agreement is under attack by many parties, critics cite concern on ethical, local culture, unpredictably changing technology, etc. The WTO-SPS approach is increasingly challenged for its balance in favor of economic consideration towards its a unique cultural identities. Food as culture and food as commerce. Dispute on Beef Hormones is the ideal example on this matter. The local perception of food and food safety, evolution of food production technologies, and security aspects of food, then being explored, in order to analyze the relationship between SPS Agreement, food tradition, science and technology. At the end, it is realized that no matter how strong the faith in science and economics, it is unwise to dismiss the deeply-rooted beliefs of many people in the world.